You need to consider the following complex number `z = x + i*y` and you need to replace it in the given equation, such that:

`(x + i*y)^2 = 2i => x^2 + 2i*x*y + (i^2*y^2) = 2i`

Replacing `-1` for ` i^2` yields:

`x^2 - y^2 + 2i*x*y = 2i`

You need to equate the real parts both...

(The entire section contains 155 words.)

## Unlock This Answer Now

Start your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.